Iowa field reports, fall 1998, Stephen Dinsmore - Dinsmore, Stephen J.et al (1999)
An annotated list of birds sighted by Stephen Dinsmore and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed